The Determinants of Environmental Disclosures of Public Listed Firms in Malaysia - Mohd Waliuddin, Mohd Razali; Samuel Tu, Ching Lee; Josephine Yau, Tan Hwang; Sharifah Sabrina, Syed Ali; Damien Iung Yau, Lee (Human Resource Management Academic Research Society (HRMARS), 2023)
Determining environmental disclosure is important because it promotes corporate transparency, ensures accountability for environmental impacts, and aids stakeholders in making informed decisions. The objective of this study is to investigate the link between specific firm attributes and environmental disclosure. A final sample of this study consists of 429 Malaysian public listed firms in the year 2016. Data on firm size, profitability, leverage and disperse share ownership were obtained from Eikon database while dependent variable which is environmental disclosure and other variables such as environmental management systems (EMS), age and auditor type were manually collected from firm annual reports. The environmental disclosure is measure based on 11 environment related-words highlighted which are energy or electric, water, biodiversity, emission, effluent, waste, recycle, reuse, spill, environmental impacts and ISO 14001. The regression results show that firm size, industry type, EMS and disperse share ownership are significantly influence environmental disclosures. This study proves that certain firm characteristics, coupled with good corporate governance mechanisms, can motivate firms to provide environmental disclosures. Further research proposes using alternative proxies for environmental disclosure to examine its relationship with foreign associations, brand awareness, firm value, and the cost of financing, which could offer new insights into environmental disclosure practices.